Furanodiene Induces Extrinsic and Intrinsic Apoptosis in Doxorubicin-Resistant MCF-7 Breast Cancer Cells via NF-κB-Independent Mechanism - Zhong, Zhang-Feng; Yu, Hai-Bing; Wang, Chun-Ming; Qiang, Wen-An; Wang, Sheng-Peng; Zhang, Jin-Ming; Yu, Hua; Cui, Liao; Wu, Tie; Li, De-Qiang; Wang, Yi-Tao (Frontiers in Pharmacology, 2017)
Chemotherapy is a primary approach in cancer treatment after routine surgery. However, chemo-resistance tend to occur with chemotherapy in clinic, resulting in poor prognosis and recurrence. Nowadays, Chinese medicine may shed light on design of new therapeutic modes to overcome chemo-resistance. Furanodiene, as a heat-sensitive sesquiterpene, is isolated from the essential oil of Rhizoma Curcumae. Even though growing evidences claimed that furanodiene possesses anti-cancer activities in various types of cancers, the underlying mechanisms against chemo-resistant cancer are not fully clear. Our study found that furanodiene could display anti-cancer effects through inhibiting cell viability, inducing cell cytotoxicity, and suppressing cell proliferation in doxorubicin-resistant MCF-7 breast cancer cells. Furthermore, furanodiene preferentially causes apoptosis by interfering with intrinsic/extrinsic-dependent and NF-κB-independent pathways in doxorubicin-resistant MCF-7 cells. These observations also prompt that furanodiene may be developed as a promising natural product for multidrug-resistant cancer therapy in the future.